2006
DOI: 10.1007/s00442-006-0409-0
|View full text |Cite
|
Sign up to set email alerts
|

Nitrogen response efficiency increased monotonically with decreasing soil resource availability: a case study from a semiarid grassland in northern China

Abstract: The concept of nutrient use efficiency is central to understanding ecosystem functioning because it is the step in which plants can influence the return of nutrients to the soil pool and the quality of the litter. Theory suggests that nutrient efficiency increases unimodally with declining soil resources, but this has not been tested empirically for N and water in grassland ecosystems, where plant growth in these ecosystems is generally thought to be limited by soil N and moisture. In this paper, we tested the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
76
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(82 citation statements)
references
References 53 publications
5
76
1
Order By: Relevance
“…1) and leaf latitudinal N:P patterns 6,8 , appear to support the geochemical hypothesis 11,14,20 , that is, tropical soils are on average geologically older, more weathered with lower supply of P relative to N, consequently resulting in higher N:P ratios in roots in tropical latitudes. The variation not explained by climate and soil (Table 2) is likely in part due to biological factors, for example, plant species (such as differences in nutrient economy), stand age and disturbance history 12,33 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…1) and leaf latitudinal N:P patterns 6,8 , appear to support the geochemical hypothesis 11,14,20 , that is, tropical soils are on average geologically older, more weathered with lower supply of P relative to N, consequently resulting in higher N:P ratios in roots in tropical latitudes. The variation not explained by climate and soil (Table 2) is likely in part due to biological factors, for example, plant species (such as differences in nutrient economy), stand age and disturbance history 12,33 .…”
Section: Discussionmentioning
confidence: 99%
“…Plant N and P stoichiometry is related to the variation among species, plant developmental stages, tissue types and environments 6,[9][10][11][12] . Plant green-leaf N and P concentrations have been shown to vary among climatic and soil environments, presumably reflecting both plant adjustment (acclimation and adaptation) 13 and biogeographical differences in relative N and P supply 14 .…”
mentioning
confidence: 99%
“…Bridgham et al (1995) gave a mathematical proof that nutrient response efficiency has to be unimodal across broad ranges of nutrient supply. However, the unimodal efficiency has not been observed for N so far and is debatable (Yuan et al 2006). A monotonic increase of NRE with decreasing soil N availability was observed by Yuan et al (2006) for Mongolian grassland.…”
Section: Introductionmentioning
confidence: 88%
“…However, a linear relationship over a wide range of N supply is unlikely given the observation that no further increase in productivity occurs at high levels of N availability (Pastor and Bridgham 1999). Studies that investigated the relationships between NRE and soil N availability found increases in NRE as soil N availability declined in an experimental plantation of tropical trees (Hiremath and Ewel 2001;Yuan et al 2006). Bridgham et al (1995) gave a mathematical proof that nutrient response efficiency has to be unimodal across broad ranges of nutrient supply.…”
Section: Introductionmentioning
confidence: 99%
“…Significant advances have been made in the past decades toward understanding the relationship between soil N and NPP in terrestrial ecosystems, whereas substantial uncertainties persist, and discrepancies between studies remain unresolved [40][41][42]. Yuan et al (2006) [43] found a significant positive linear correlation between NPP and soil inorganic N for grassland ecosystems in Mongolia, whereas Luo et al (2004) [10] found a curved relationship between NPP and total soil N. Our field data indicated that N soil alone explained nearly 10.6% of the NPP variation within the transect ( Figure 4, Table 2). Hobbie (2015) [23] focused on feedback to NPP operating through litter decomposition, and reported that positive or negative effects of litter N on the later stages of litter decomposition could strengthen or weaken the positive loop of NPP.…”
Section: N Controlmentioning
confidence: 99%